Research on the mechanism of core acupoints in electroacupuncture for functional constipation based on data mining and network acupuncture - Ong, Shun Seng; Tang, Ting; Xu, Lianjie; Xu, Canwei; Li, Qi; Deng, Xiaoyue; Shen, Peihua; Chen, Yi; Song, Yang; Lu, Hai; Fang, Ling (Frontiers in Medicine, 2024)
FC is a common gastrointestinal disorder that imposes a considerable strain on global health. I Electroacupuncture (EA), with its precise stimulation control and standardized protocols, shows promise in FC management. However, optimal EA parameters for FC treatment are yet to be established. Our study reviews EA applications in FC to inform a standardized treatment approach and explore EA's therapeutic mechanisms. Methods This comprehensive study utilized research literature from databases including PubMed, Embase, OVID, Web of Science, the Cochrane Library, CNKI, VIP, and Wanfang to perform a descriptive analysis of acupoint selection and EA parameters. It proceeded to analyze high-frequency acupoint groupings and stimulus parameters, followed by the excavation and analysis of core acupoint prescriptions. Subsequent steps integrated potential target identification for these core formulas, the assembly of a “core acupoint-prescription-target-constipation” network, and the construction of a protein-protein interaction (PPI) network to extract central targets. Additionally, Gene Ontology (GO) and KEGG enrichment analyses were conducted to prognosticate the underlying mechanisms by which EA may exert its therapeutic effects on FC. Results In our study, we analyzed 141EA prescriptions for FC and identified a core set of acupoints including Tianshu (ST25), Fujie (SP14), Shangjuxu (ST37), and Zusanli (ST36) through data mining. The frequency of use was highest for Tianshu (ST25) with 119 occurrences, followed by Fujie (SP14) with 59, Shangjuxu (ST37) with 42, and Zusanli (ST36) with 23. PPI network analysis revealed key targets such as NFKB1, IL6, MyD88, TLR4, TNF, TLR2, and IL1B. GO and KEGG analyses of 49 constipation-associated targets identified 257 BP, 37 CC, and 41 MF terms, and 154 significant pathways, with the top 20 visualized for further analysis. Conclusions The core acupoint prescription of EA for FC can exert its therapeutic effects by acting on multiple targets and pathways synergistically especially on NFKB1, IL6, MyD88, TLR4, TNF, TLR2, and IL1B. The research findings have preliminarily validated the fundamental effects and related mechanisms of EA parameters and core prescriptions, providing direction for further in-depth exploration of the mechanisms of action.